4 Morquio Syndrome and Gastric Adenocarcinoma: Is There an Association?. (11th January 2018) - Hamza, Ameer; Ibrahim, Ahmad; Edens, Jacob; Lalonde, Crystal; Danforth, Robert
Abstract: Morquio syndrome is a rare autosomal recessive lysosomal storage disease/mucopolysaccharidosis (MPS). Specifically it is MPS type IV, and is further divided into IVA and IVB subtypes depending on the enzyme deficiency. Type IVA is caused by deficiency of enzyme N-acetyl-galactosamine-6-sulfatase causing intracellular accumulation of keratan sulfate, whereas type IVB is caused by β-galactosidase deficiency. Patients with Morquio syndrome present with musculoskeletal abnormalities, such as signs of muscular atrophy, pectus carinatum, dysostosis multiplex, odontoid hypoplasia, short stature, dorsolumbar kyphoscoliosis, and waddling gait. Atlantoaxial subluxation leading to spinal cord compression in the upper cervical region can be life threatening. This is a consequence of odontoid dysplasia, a major complication of MPS type IV. The manifestations that may develop later in the life include corneal opacity, deafness, hypermobility of joints, cardiac abnormalities, quadriplegia, and respiratory paralysis. Historically Morquio syndrome has not been associated with carcinomas or other malignancies. Thorough search of literature revealed only 1 case of osteosarcoma of right femur in an 18-year-old man with Morquio syndrome. We present a case of a 30-year-old African American man with Morquio syndrome and widespread metastatic gastric adenocarcinoma. The patient was diagnosed with poorly differentiated gastric adenocarcinoma in June 2015 and received chemoradiotherapy. The disease, however, persisted. Later, the patient was admitted with back pain and shortness of breath. His condition deteriorated during the course of hospitalization, and he expired on hospital day 10. An autopsy was performed. Significant findings at autopsy included poorly differentiated gastric adenocarcinoma metastatic to left supraorbital dura, pituitary gland, pericardium, bilateral lungs, liver, peripancreatic soft tissue, colon, bilateral periadrenal soft tissue, thoracic vertebrae, periprostatic soft tissue, and urinary bladder. The immediate cause of death was widespread metastatic disease; however, complications of MSP IV contributed significantly. The association between MSP IV and malignancy requires further studies.